Fitness for work in health care workers: biological risk / Giudizio di idoneità e rischio biologico - Porru, S.; Micheloni, G.P.; Carrer, P. (La Medicina del Lavoro, 2012)
The aim of this contribution is to propose good medical practice in formulating and managing fitness for work (FFW) for health care workers exposed to biological agents. A literature review was conducted, together with a critical analysis of available scientific evidence and presentation of practical examples taken from the Italian multicentric study in which the authors have been participating since 2008. Within the health care sector and with special reference to biological risk, making and subsequently managing a FFW for a specific job is in fact a particularly arduous task for the occupational physician and for the entire hospital management system. The process that leads to issuing a FFW needs to follow the appropriate guidelines and good technical and scientific practice and also take into careful consideration current legislation (national, regional, etc); it is the result of a well grounded balance between professional ethics, rights and duties of the worker and patient, but also of the employer and of all those involved. All these aspects need to be adapted to the single work situations, applying the principle of precaution and careful flexibility in management, with accurate evaluation of each individual clinical case with its peculiarities and referral, where necessary, to expert opinion. It is also indispensable to have in place a clear and jointly agreed hospital management policy where co-responsibility is taken by each single actor, always with due respect for specific roles, so that the Occupational Physician  and employers are not left to manage the issue alone.Giudizio di idoneità e rischio biologico negli operatori sanitariScopo di questo contributo è proporre buone prassi nella formulazione e gestione del giudizio di idoneità negli operatori sanitari esposti ad agenti biologici.È stata condotta una  revisione della letteratura, congiuntamente ad un’analisi critica delle evidenze scientifiche disponibili, valutazione indicazioni dalla pratica sul campo, con  riferimento allo studio multicentrico italiano cui gli autori da tempo contribuiscono. Nel settore della sanità, con particolare riferimento al rischio biologico, la formulazione e la successiva gestione del giudizio di idoneità alla mansione specifica è infatti particolarmente impegnativa per il medico del lavoro/competente e per l’intero sistema gestionale aziendale. Il processo che porta alla formulazione del giudizio di idoneità deve essere indirizzato da linee guida e da buone prassi tecnico-scientifiche ed attento a quanto previsto dalla legislazione (nazionale, regionale, ecc.), frutto di un bilancio motivato tra etica/deontologia professionale, diritti e doveri del lavoratore/paziente, ma anche del datore di lavoro e di tutti gli attori coinvolti a vario titolo nel processo e tutela della riservatezza. Tali aspetti dovranno essere adattati alle singole realtà operative, applicando il principio di precauzione e con attenta flessibilità gestionale, valutando sempre accuratamente il singolo caso clinico con le sue peculiarità, ricorrendo ove necessario al parere di esperti. È inoltre indispensabile una chiara e condivisa politica aziendale, in cui vi sia un’assunzione di co-responsabilità dei singoli protagonisti, nell’indispensabile rispetto degli specifici ruoli, affinché il medico del lavoro/competente e i datori di lavoro non siano lasciati soli a gestire la tematica.